PEMAHAMAN KEARIFAN LOKAL DI SEKOLAH DASAR SEBAGAI SUATU CARA MEMBENTUK KARAKTER SISWA - Ramadan, Zaka Hadikusuma (Jurnal Pendidikan Guru, 2017)
Prospects local knowledge is very dependent on how communities preserve local wisdom back and how people change their mindset back to the holistic mindset. So that the natural resources and the natural environment in the communities can be utilized and preserved without disturbing the balance. Regulation of the Minister of Education and Culture, Number 54 of 2013 on competency standards primary and secondary education. Stated that graduates SD / MI / SDLB / Package A has the attitude, knowledge and skills. Elementary school age (approximately ages 6-12) is an important stage in the implementation of character education, even fundamental to the success of the character development of students. Children are a national asset that needs to be saved. Since early need to be introduced on ethical values, moral values are high, through the activities of cultural preservation of their local or regional culture. It is unfortunate if only the pursuit of academic education only. Though the success of education must be balanced between academic and non-academic.